Anesthetic and Obstetrical Factors Associated With the Effectiveness of Epidural Analgesia for Labor Pain Relief: An Observational Population-based Study. Issue 4 (December 2017) - Bonnet, M.P.; Prunet, C.; Baillard, C.; Kpéa, L.; Blondel, B.; Le Ray, C.
Abstract : ( Reg Anesth Pain Med . 2017;42(1):109–116) Epidural analgesia is considered the gold standard for pain relief during labor due to its high rate of maternal satisfaction and minimal side effects for both mother and child. However, pain relief during labor is a complex issue and there continues to be efforts to improve epidural analgesia. Many factors can influence maternal satisfaction with their epidural labor analgesia, including the place of delivery, hospital staff behavior, adverse effects, efficacy, and the woman's involvement in decision-making. This secondary analysis of a population-based study aimed to identify factors associated with successful epidural analgesia, considering both efficacy and maternal satisfaction.